Growing as a Teacher - Beck, Clive. author. aut Link
XXXII, 172 p.
Keywords: Teacher learning doesn’t end with initial preparation; many insights and skills remain to be added. This book is concerned with ongoing teacher learning, its goals (Part I) and pathways (Part II). It is based on a longitudinal study of 42 teachers: 20 over their first 8 years of teaching and 22 over their first 5 years. The areas of continued teacher learning identified in our study were: vision of teaching, program planning, assessment, relevance, subject content and pedagogy, classroom organization and community, inclusion, and professional identity. The pathways of learning included informal and formal PD, teacher inquiry, and school-based learning. A key finding of our research was that, over the years, teachers learn a great deal informally. However, they do so largely on their own and under considerable stress. Teachers need more support than they currently receive, both for survival and to enhance their informal learning. Teachers can benefit significantly from external input, but their everyday learning makes them key “experts” in teaching. Accordingly, PD providers should work with teachers, utilizing their existing knowledge. This book is written for consideration by teachers, student teachers, teacher educators, PD providers, policy developers, and others interested in facilitating teacher learning. Some of us have been writing – somewhat desperately – on these ideas for years. Beck and Kosnik have given us strong evidence that the ideas are effective in practice. I hope this persuasive and beautifully written book will be widely read.Nel Noddings, Lee Jacks Professor of Education Emerita, Stanford University This book makes a powerful case for taking teachers’ professional development seriously. It brings us the voices of beginning teachers as they deepen their professional knowledge over time and makes clear the depth of commitment they bring to the job. Professor Gemma Moss, Institute of Education, University of London.